Combining ability for yield and plant phenology in plantain derived populations - Tenkouano, T.; Ortíz, R.; Vuylsteke, D.R. (1998)
Genetic enhancement of Musa spp. has aimed at producing hybrids with high yield, short stature, fast crop cycling, and disease resistance through interspecific and interploidy crosses. Progeny testing for parental selection has seldom been carried out in Musa and little is known on combining ability and heterosis in this species. A 5 _ 5 factorial mating design was used to estimate components of phenotypic variance in 4x-2x hybrid populations and to determine the combining ability of their progenitors for yield and associated traits. General combining ability was much greater than specific combining ability for these traits, and, therefore, only little recombinative heterosis could be expected upon crossing. Thus, the 4x-2x breeding scheme should aim to accumulate favourable alleles in 4x and 2x clones through recurrent selection. Such clones could be used per se or in crosses aimed at restoring the seedlessness character in the progeny due to female sterility in a triploid background.